An adaptive error correction system for microwave transmission systems - Cheah C.L.; Tiong S.K. (2023)
This paper proposes an adaptive error correction system for microwave transmission systems. Unlike most previous adaptive error correction systems which change to a stronger code for error correction based on either packet losses or erroneous condition, the proposed system is able to do so before an error occurs. Simulation results show that the proposed system can maintain the output bit error rate (BER) below a target BER by assigning an appropriate value of waiting delay before changing to a weaker code.